2020
DOI: 10.1101/2020.03.31.20047126
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge and Beliefs towards Universal Safety Precautions to flatten the curve during Novel Coronavirus Disease (nCOVID-19) Pandemic among general Public in India: Explorations from a National Perspective

Abstract: Background:The novel Coronavirus disease is being considered as the most serious health threat that the world has never witnessed in the recent times and significantly affecting the daily routine of mankind by emerging as a global pandemic. Yet, as there is no treatment nor a vaccine that was approved so far, universal safety precautions (USPs) and mitigating strategies are the only way to deal with this emergency crisis. However, knowledge and beliefs towards USPs among the general public in countries such a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
2
11
1
1
Order By: Relevance
“…Similar studies conducted in Jordan (17,18), Viet Nam (19), China (20) and India (21,22) also discovered better knowledge among educated people who have access to reliable information. Younger adults, males and those who were unemployed had a lower level of knowledge about COVID-19 in our study population.…”
Section: Discussionsupporting
confidence: 64%
“…Similar studies conducted in Jordan (17,18), Viet Nam (19), China (20) and India (21,22) also discovered better knowledge among educated people who have access to reliable information. Younger adults, males and those who were unemployed had a lower level of knowledge about COVID-19 in our study population.…”
Section: Discussionsupporting
confidence: 64%
“…There have been fundamental changes to society with the emergence of the SARS-CoV-2 global pandemic. [1][2][3][4] As COVID-19 has no specific antiviral drug treatment or vaccine to date, universal safety precautions and mitigating strategies are the only common way to deal with this global health emergency. 4 As COVID-19 outbreak posed significant challenges for the public health, research and medical communities, governmental policies and processes were introduced to curtail the spread of the virus across the nations of the world.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] As COVID-19 has no specific antiviral drug treatment or vaccine to date, universal safety precautions and mitigating strategies are the only common way to deal with this global health emergency. 4 As COVID-19 outbreak posed significant challenges for the public health, research and medical communities, governmental policies and processes were introduced to curtail the spread of the virus across the nations of the world. 5 This included instituting temporary restrictions on travel with dramatic reduction in the number of travellers, self distancing, self isolation, quarantine of international travellers, regular hand washing and the use of face masks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…53 A survey conducted in March 2020 found that 75% of the public believed that masks should be worn even by asymptomatic people, and 77% of respondents indicated that the N95 mask was most protective. 74 By May 9, the per-capita mortality was 1.5 per million.…”
Section: Resultsmentioning
confidence: 99%